Reversible data hiding based on histogram modification of difference images by s-type and Hilbert curve scanning - Chen, Jin; Ye, Ruisong (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Reversible data hiding technology has currently attracted great attention recently. Using reversible data hiding methods,Â original cover images can be recovered losslessly from the cover image embedded information. In this paper, spatialÂ reversible data hiding schemes based on histogram modification of difference images are discussed, in which the pixelÂ gray values of difference image are altered slightly to perform the embedding and extraction. Specifically, we design twoÂ reversible data hiding schemes based on S-type scanning and Hilbert curve scanning, and compare them with the reversibleÂ data hiding scheme by difference between adjacent columns of the cover image. Embedding capacity and PSNRÂ are calculated to figure out how block size, difference manner and embedding level influence the effect of hiding.